Efficacy of a Neurofeedback Training on Attention and Driving Performance: Physiological and Behavioral Measures - Balconi, Michela; Crivelli, Davide; Angioletti, Laura (Frontiers in Neuroscience, 2019)
Increased attention and lower stress levels are associated with more functional and safe driving behavior, since they contribute reducing distractibility and risk-taking at the wheel. Previous neuroscience research highlighted that NeuroFeedback (NF) training mediated by wearable devices could be effective in terms of neurocognitive strengthening and attention regulation with direct effect on driving attentional performance. This research aims to test the effectiveness of a NF protocol on a sample of drivers, to observe its impact on attentional skills and psychophysiological levels of stress involved in driving behavior. 50 participants were randomly assigned to the experimental and active control group. The experimental condition consisted of a 21-day mindfulness NF training with incremental duration sessions. A pre- (t0) and post-treatment (t1) assessment included behavioral, psychometric, neuropsychological, and psychophysiological autonomic measures. Driver Behavior Questionnaire (DBQ) and Active Box (AB) device were used to evaluate the everyday driving behavior. Results underlined an improvement in driving behavior performance and a decrease of violations at the wheel of the experimental group at t1 measured respectively by AB and DBQ. About the autonomic and neuropsychological measure, an increase in Heart Rate (HR) and an increased accuracy at the Stroop Task were detected: a specific increase of Stroop-related HR was found for the experimental group at t1. Reduced reaction times were found in the Multiple Features Target Cancellation for the experimental group at t1. The experimental group displayed a physiological, behavioral and neuropsychological increased efficiency related to attention as well as a driving-related behavioral improvement after NF training.